Assessing Disability Empowerment Initiatives: A Case Study of the Difabis Program in Jakarta - Faizi Faizi; Siti Wardah (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
The Difabis program, initiated by Badan Amil Zakat Nasional (BAZNAS) DKI Jakarta, Indonesia’s National Zakat Agency at the provincial level, aims to empower individuals with disabilities through entrepreneurship and workforce integration. This qualitative case study evaluates the effectiveness of the program using Gibson's (1992) framework, which assesses seven indicators: clarity of purpose, clarity of strategy, process analysis and policymaking, comprehensive planning, establishment of appropriate programs, availability of facilities and infrastructure, and monitoring and control systems. Data were collected through semi-structured interviews with four participants (one BAZNAS administrator, two beneficiaries, and one academic), passive participant observation at two Difabis branches, and a document analysis of program reports and policies. The findings indicate that the program aligns with several empowerment indicators, demonstrating strengths in the clarity of purpose, strategic coherence, comprehensive planning, and infrastructure provision. Participants reported enhanced skills, income stability, and self-esteem, underscoring the program's role in promoting financial autonomy and social inclusion. However, gaps were identified in the process analysis and policy formulation, particularly in the reliance on self-reported data for beneficiary targeting, which risks excluding the most vulnerable groups. The program's innovative fusion of zakat redistribution with skill development offers a replicable model for Muslim-majority contexts, but its long-term sustainability and scalability remain unexamined. Despite limitations in generalizability and comprehensiveness, this study contributes to the literature on disability empowerment by highlighting the potential of faith-based initiatives to address intersectional marginalization. This study offers a novel contribution by being the first to evaluate a disability-empowerment zakat program using Gibson’s (1992) organizational effectiveness framework, thereby bridging faith-based social finance and disability empowerment studies.